The Ladybird Book of Spelling and Grammar - Audrey Daly (Italy Ladybird Books Ltd., 1999)
Whether it is a letter to your friend, a note to your mum, or a story you want to write, you will always need to use good English. This book has all the rules and the information you need to write clearly and effectively, with the tips to make it easier.
Keywords: Level Reader -- Level Reader